Active crustal deformation model of the Fen–Wei rift zone, North China: Integration of geologic, geodetic, and stress direction datasets - Song, Shangwu; Li, Yuhang; Hao, Ming (Frontiers in Earth Science, 2022)
The Fen–Wei rift zone (FWRZ) of North China is an important zone of active crustal deformation representing a transition from extrusion tectonics related to the Tibetan Plateau to subduction tectonics related to the potential far-field influence of the west Pacific plate. In this study, we determined the kinematic constraints of active crustal deformation in the FWRZ, which are fundamental for forecasting seismicity. NeoKinema, a kinematic finite-element model, was employed to estimate the long-term fault slip rates, distributed crustal deformation field, and on- and off-fault strain-rate fields in the FWRZ by fitting updated geological fault slip rate, geodetic GPS velocity, and principal compressive stress direction datasets. Our results show that the FWRZ is a characteristic low-strain kinematic setting, with most active faults exhibiting slip rates of less than 1 mm/a. The total sinistral shear rate from the southern Ordos block to the Qinling Mountains is approximately 1 mm/a, indicating limited tectonic extrusion along the EW-trending Qinling Mountains. Additionally, the central Shanxi rift exhibits prominent dextral shear of ~0.5 mm/a that decreases toward its north and south ends, corresponding to crustal extension of 1.1–1.2 mm/a in the Datong and Yuncheng basins, respectively. However, this significant crustal extension cannot be solely attributed to terminal effects caused by dextral shear in the central Shanxi rift. A comparison between predicted seismicity and historical earthquake records reveals some remarkable seismic gaps, particularly in the Datong, Hancheng, and Yuncheng basins, indicating higher seismic potential in these locations. This study provides insights into the long-term crustal deformation processes and regional seismic potential of the FWRZ.